Effects of Ketoprofen Administration on Relation between Acute Phase Proteins and Metabolic Parameters in Cows during Early Lactation - Kovacevic, Zorana; Belic, Branislava; Cincovic, Marko R.; Stojanac, Nenad; Stevancevic, Ognjen; Erdeljan, Mihajlo; Davidov, Ivana; Stojanovic, Dragica (Acta Scientiae Veterinariae, 2019)
Background: Acute phase proteins (APPs) are clinically useful parameters for measuring the occurrence and severity of inflammatory responses in cattle. As large group of proteins, APPs are mainly secreted by hepatocytes whose concentration increase or decrease as response to tissue injury, inflammation or infection. The transition from late pregnancy to early lactation is associated with a compromised immune status coupled with increased acute phase response. Non-steroidal anti-inflammatory drugs (NSAIDs) are used in treatment of inflammatory conditions. The main objective of the present study was to analyze the effects of a preventive administration of the NSAID (ketoprofen) in post-calving dairy cows on concentration of APPs (haptoglobin and fibrinogen) and their relationship with indicators of liver function. Materials, Methods & Results: The treatment group (n = 15) was given an intramuscular injection of ketoprofen in the concentration of 3 mg/kg during three consecutive days after calving. The control group (n = 15) was not treated with ketoprofen. Blood samples were taken from coccygeal vein, on the first day of treatment and in the first and second week postpartum and they were analyzed for metabolic parameters (albumin and aspartat aminotransferaze) and APPs such as haptoglobin and fibrinogen. Compared with control, ketoprofen administration decrease the levels of haptoglobin and fibrinogen and AST activity. Increase in albumin concentration was recorded in experimental group of cows compared with control. Negative correlations (P < 0.01) were found between the haptoglobin concentration and albumin concentration and aspartate aminotransferaze activity. Discussion: As inflammatory indicator in dairy cows, it is recorded that serum concentrations of haptoglobin is increased during mastitis. Beside haptoglobin, fibrinogen represents one of the APPs whose serum concentration increases during response in the acute phase. During the first and second week after partus, in cows with acute puerperal metritis, an increase in fibrinogen concentration was observed in relation to clinically healthy animals. Based on our results, it can be concluded that an intramuscular injection of ketoprofen (3 mg × kg. bw.-1) administered in cows in the first days following parturition reduces the concentration of some APPs (haptoglobin and fibrinogen). In regard to Hp concentration, the treatment success agreed with previous results using i.m. acetyl-lysine salicylate during the first 5 days of lactation. Reduction in APPs concentration in our research results could be attributed to the anti-inflammatory effect of ketoprofen. In addition, use of ketoprofen reduces the intensity of relationship between inflammatory markers and indicators of liver funcition. Impaired functional capacity of the liver may be associated with reduced albumin concentration in the peripartal period, and during inflammatory or infectious diseases. Increase in albumin concentration in experimental group of cows compared to the control in our research could be attributed to the anti-inflammatory effect of ketoprofen. Hence it can be concluded that the use of ketoprofen immediately after calving reduces the intensity of relationship between inflammatory marker liver function and that NSAID treatment could be used in in improving animal well-being and controlling of the occurence and intesity of postpartum diseases.